Volume changes in leg muscles during ski-specific motions as a basis for optimized junction in preventive knee bracing - Olvermann, M.; Spitzenpfeil, P.; Härter, E.; Diez, L.; Huber, A.; Brucker, P. U. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Most injuries in alpine ski world cup are knee injuries (36%) and more than half of them lead to a break of more than 28 days (Flørenes et al., 2009). These numbers can be potentially reduced by usage of an effective knee brace which - at the same time - needs to be non-disturbing. This study examines for the first time the changes in soft tissue volume of the leg in different ski-typical positions to enable an optimized junction between the leg and prospective knee braces.